TINDAK PIDANA (TINJAUAN YURIDIS PASAL 7 AYAT (1) HURUF J UNDANG-UNDANG NOMOR 8 TAHUN 1981 TENTANG KUHAP) - Nur Fatimah (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
AbstractIn article 7, paragraph (1) of the code of criminal procedure stated that the letter j investigators as stipulated in article 6 paragraph (1) letter a because of its obligations has the authority "to conduct another action according to the law is responsible”. Listen to the duties and authorities of the police apparatus as set forth above, then the one question that arises here is inserting a perpetrator into the People Search listings is another action of investigators in solving the crime. For that I need to know how to set The search list as another action investigator responsible according to the law and how the terms to define other actions investigators in conducting The search list. In the Act No. 2 of 2002 on the State police of the Republic of Indonesia, the police authority to conduct the search list of The assignment is not set explicitly, but when looking at the provisions of article 16 paragraph (1) letter I Act No. 2 of 2002 jo article 7 paragraph (1) of the code of criminal procedure, there is a letter of authority to perform another action according to the law is responsible. Whereas the conditions to be met by investigators in conducting The search list against That in The search list has been representing suspects and Investigators have done maximum effort looking for a suspect by way of official or directly calling looking for suspects in his residence, but did not attend. Keywords: People Search list , the code of criminal procedure, suspects, investigators, criminal acts.